2008
DOI: 10.1148/radiol.2471070591
|View full text |Cite
|
Sign up to set email alerts
|

31P MR Spectroscopic Assessment of Muscle in Patients with Myasthenia Gravis before and after Thymectomy: Initial Experience

Abstract: Mild-MG group patients have muscle oxidative metabolism similar to that of healthy control subjects, whereas moderate-to-severe-MG group patients have impaired V(max) during exercise and a noticeable shift to glycolytic metabolism, but these abnormalities are reversible after thymectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Kreis et al showed that CP peak on proton MRS of human muscle reflected phosphocreatine rather than creatine levels [21], thus decrease of CP peak in our MG patients was probably due to decrease in phosphocreatine. Previous 31 P spectroscopic study demonstrated poor phosphocreatine recovery during exercise in calf muscles of patients with moderate to severe MG reflecting the presence of mitochondrial dysfunction [22]. Impaired mitochondria probably fails to shift fuel utilization from carbohydrates to lipids [13] and it may be a reason for accumulation of IMCL (and maybe EMCL) in muscles of patients with both forms of MG. Mitochondrial abnormality has been the most frequently reported alternative mechanism in pathogenesis of MG so far [7,20,21] and we found it in both investigated forms of MG.…”
Section: Discussionmentioning
confidence: 94%
“…Kreis et al showed that CP peak on proton MRS of human muscle reflected phosphocreatine rather than creatine levels [21], thus decrease of CP peak in our MG patients was probably due to decrease in phosphocreatine. Previous 31 P spectroscopic study demonstrated poor phosphocreatine recovery during exercise in calf muscles of patients with moderate to severe MG reflecting the presence of mitochondrial dysfunction [22]. Impaired mitochondria probably fails to shift fuel utilization from carbohydrates to lipids [13] and it may be a reason for accumulation of IMCL (and maybe EMCL) in muscles of patients with both forms of MG. Mitochondrial abnormality has been the most frequently reported alternative mechanism in pathogenesis of MG so far [7,20,21] and we found it in both investigated forms of MG.…”
Section: Discussionmentioning
confidence: 94%
“…Muscle paralysis with μ -conotoxin GIIIB, a toxin that blocks muscle-specific voltage-gated Na + channels without affecting neuronal function [ 37 ], decreased nerve-evoked ATP (~15%) and ADO (>90%) outflow [ 7 ]. Moderate-to-severe MG patients have impaired oxidative metabolism and a noticeable shift to glycolytic metabolism during exercise, which yields to higher-end Pi/ATP ratio and reduced levels of synaptic ADO levels [ 38 ]. Besides the fact that exocytosis of ATP may occur synchronously with ACh in a frequency-dependent manner [ 13 , 39 ], the nucleotide may also be released by tetanic stimulation of skeletal myotubes from healthy animals, through pannexin-1 hemichannels, within a 15 s to 3 min time scale [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Long measurement times and relatively low spatial resolution have limited the clinical use of 31 P-MRS (3)(4)(5)(6). Nevertheless, some groups have proved the clinical value of 31 P-MRS for the assessment of metabolic disorders (7)(8)(9) or oncology (2). 31 P-MRS significantly benefits from higher magnetic field strengths (i.e., 7 T) (10)(11)(12).…”
mentioning
confidence: 99%